1992
DOI: 10.1164/ajrccm/146.6.1576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cor Pulmonale on a Modified Short-axis Section of the Heart by Magnetic Resonance Imaging

Abstract: Magnetic resonance imaging (MRI) of a modified short-axis section of the heart, in 36 patients with chronic pulmonary diseases, consisting of 19 patients with pulmonary hypertension (PH group; mean pulmonary arterial pressure > or = 20 mm Hg) and 17 patients without pulmonary hypertension (non-PH group) was evaluated to study the configuration of the right ventricle. Parameters of right ventricular hypertrophy, including right ventricular wall thickness (RVWT) and the ratio of RVWT to left ventricular posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…In other words, thickening of the RV wall is caused by RV pressure overload, as in the left ventricle. Saito et al [23] demonstrated that there were significant correlations between RV wall thickness evalu ated by magnetic resonance imaging (MRI) and PAm or total pulmonary resistance or pulmonary arteriolar resis tance. Although we did not perform thallium myocardial scintigraphy and MRI, and pulmonary hypertension was generally mild to modest in our cases, the following was speculated: RV hypertrophy according to the degree of pressure overload exists in our CPD and PTE patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, thickening of the RV wall is caused by RV pressure overload, as in the left ventricle. Saito et al [23] demonstrated that there were significant correlations between RV wall thickness evalu ated by magnetic resonance imaging (MRI) and PAm or total pulmonary resistance or pulmonary arteriolar resis tance. Although we did not perform thallium myocardial scintigraphy and MRI, and pulmonary hypertension was generally mild to modest in our cases, the following was speculated: RV hypertrophy according to the degree of pressure overload exists in our CPD and PTE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricular end-diastolic wall thickness has been shown to correlate well with MPAP in primary pulmonary hypertension (PPH) and some causes of secondary pulmonary hypertension [17][18][19]. A linear relationship between RVM and MPAP has been described for PPH but not for other forms of PAHT [8].…”
mentioning
confidence: 99%
“…Several estimators based on different MRI techniques have been described in recent years, including acceleration time (the time of onset of forward flow to the moment of maximum flow velocity in the main pulmonary artery), acceleration time/ejection time ratio, pulse wave velocity, cross-sectional area of the main pulmonary artery and ventricular mass index. Right ventricular end-diastolic wall thickness has been shown to correlate well with mean Ppa in idiopathic pulmonary arterial hypertension and some cases of secondary pulmonary hypertension [58,59]. A linear relationship between right ventricle mass and mean Ppa has been described for idiopathic pulmonary arterial hypertension [13].…”
Section: Ppa Estimation By Cmrmentioning
confidence: 97%